Positive electrode, preparation method thereof and lithium battery
By using a positive electrode material with the same crystal structure as the lithium supplement agent in the positive electrode material layer of the lithium battery, and introducing a specific type of lithium supplement agent into the coating layer, the loss of lithium elements in the first operation and subsequent cycles of the lithium battery is solved. The problem of this achieves the effect of improving the energy density and cycle life of lithium batteries.
Patent Information
- Application Number
- CN202411546654.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to a positive electrode and a preparation method thereof, and a lithium battery. Background Art
[0002] Lithium batteries are widely used in 3C digital, energy storage and automotive power due to their advantages such as good cycle performance, high energy density, high output voltage and low self-discharge. In order to meet the growing energy demand, the development of lithium batteries with high energy density and long cycle life has become a key goal. However, due to inevitable parasitic reactions, lithium batteries always suffer from the loss of active lithium, which is the main reason for the weakening of lithium battery performance.
[0003] Lithium batteries can balance such problems by providing sufficient lithium in the anode. However, the instability and fragility of lithium metal in the air means that excessive addition of lithium to the positive electrode coating is not a solution to the reduced energy density and cycle life of lithium batteries.
[0004] CN109713367B discloses a solution to improve the energy density and cycle life of lithium batteries, which provides a silicon-containing positive electrode coating material. This strategy does not fundamentally solve the problem of lithium deficiency when the lithium battery is first operated, but only solves the problem superficially.
[0005] The working principle of lithium batteries refers to the process of lithium ions migrating from the positive electrode material (such as lithium iron phosphate or lithium cobalt oxide) to the negative electrode positive electrode material (such as graphite) during the charging process. Specifically, when the lithium battery is charged, the lithium ions in the positive electrode material are released, transferred to the negative electrode through the electrolyte (usually a mixture of organic solvents and lithium salts), and then embedded in the structure of the negative electrode material. During the discharge process, the lithium ions are deintercalated from the negative electrode material, transferred to the positive electrode through the electrolyte, and recombined with the positive electrode material. This process is reversible, so lithium batteries can be charged and discharged many times. The mechanism of lithium replenishment in lithium batteries is the key to the ability of lithium batteries to achieve charge and discharge cycles, and it is also one of the reasons why lithium batteries have high energy density and long cycle life.
[0006] Many current studies have placed the lithium replenishment process in the positive electrode slurry, by adding some lithium replenishment materials to the positive electrode slurry to provide sufficient sacrificial lithium ions for the first battery charge and discharge, thereby achieving the purpose of lithium replenishment. However, this strategy has the following problems: 1. The main material in the positive electrode slurry is the positive electrode material (such as lithium iron phosphate), which has poor conductivity, while the lithium replenishment material is often insulating, which will affect the electrical performance of the battery to a greater extent; 2. Adding lithium replenishment materials to the positive electrode material will reduce the mechanical strength of the coating, thereby affecting the subsequent processes of battery production.
[0007] Therefore, it is necessary to provide an effective lithium replenishment strategy to enable the battery to have high energy density and cycle life, which is a technical problem that needs to be solved urgently. Summary of the invention
[0008] In view of the above problems existing in the prior art, the object of the present invention is to provide a positive electrode and a preparation method thereof and a lithium battery.
[0009] To achieve the above object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a positive electrode, comprising a current collector and a positive electrode material layer coated on the surface of the current collector, the positive electrode material layer comprising a positive electrode material, the current collector comprising a current collector substrate and a conductive coating disposed on the current collector substrate, the conductive coating comprising a first conductive agent and a lithium replenisher, at least one of the positive electrode materials and the lithium replenisher having the same crystal structure.
[0011] In the present invention, the same crystal structure can be the same substance or different substances, as long as the crystal structure is the same. Exemplarily, the substance with the same crystal structure can be a phosphate-based positive electrode material, such as lithium iron manganese phosphate and lithium iron phosphate, both of which belong to the olivine crystal structure. It can also be a ternary positive electrode material, such as lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide, both of which belong to the layered crystal structure.
[0012] It should be noted that for a certain substance, the substance obtained after element doping has the same crystal structure as that before doping. For example, LiNi 0.8 Co 0.1 Mn 0.1 O2 and LiNi 0.8 Co 0.1 Mn 0.05 Zr 0.05 O2 belongs to the same crystal structure.
[0013] The present invention does not specifically limit the type of the current collector substrate. For example, it can be an aluminum current collector or other composite current collectors. Those skilled in the art can choose according to their needs.
[0014] The present invention introduces and uses a specific type of lithium replenisher in the carbon coating layer and uses it in combination with the first conductive agent, so that the carbon coating layer not only plays its role in improving the conductivity of the positive electrode, but also has the function of replenishing lithium. This method basically does not affect the electrical performance of the battery, and at the same time has a good lithium replenishing effect, replenishing the lithium ions missing in the lithium battery during the first operation and subsequent cycles, avoiding lithium ion loss, enabling the lithium battery to have a higher initial efficiency, and effectively increasing the cycle life of the battery and the energy density during operation.
[0015] In the present invention, the lithium supplement agent and at least one positive electrode material in the positive electrode material layer need to have the same crystal structure, because: usually, the lithium supplement agent generally selects inorganic metal compounds such as anhydrous LiCl, LiOH, lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4), lithium iron oxide (LiFe5O8), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), lithium cobalt nickel oxide (LiCoNiO2), lithium iron nickel oxide (LiFeNiO2), etc., these materials all contain Li element, during the first charge and discharge process of the lithium battery, the Li element in the carbon coating layer can supplement the lack of Li in the positive electrode, and play a role in lithium supplement. However, this type of material is not the best choice, because during the operation of the battery, because the carbon coating layer material and the positive electrode material are different, it will affect the electron transfer rate. At the same time, the purpose of the carbon coating layer is to provide conductivity for the positive electrode. However, most aqueous solutions of lithium salts are alkaline or weakly alkaline, which affects the microstructure morphology of the conductive agent in the carbon coating layer, affects the sample structure of the carbon coating layer, and increases the interface resistance between the carbon coating layer and the electrode material layer. Therefore, the addition of inorganic metal compound lithium supplements will change the internal element structure of the carbon coating layer, thereby affecting the battery efficiency, which is not worth the loss. The present invention uses a material with the same crystal structure as at least one positive electrode material in the positive electrode material layer to supplement lithium. Substances with the same crystal structure have the principle of similar compatibility, and the same crystal structures have high anisotropy consistency, which is more conducive to increasing the lithium ion transmission speed and reducing the repulsiveness of the electron output process. Therefore, the method of the present invention can replenish the lithium element lost during the first operation of the battery and subsequent cycles without reducing the electrical performance of the battery.
[0016] Preferably, the crystal structure is selected from any one of a layered structure, a spinel structure or an olivine structure.
[0017] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0018] Preferably, the particle size of the lithium supplement meets the following requirements: D50 is 13μm-17μm, for example, it can be 13μm, 13.5μm, 14μm, 14.5μm, 15μm, 15.5μm, 16μm, 16.5μm or 17μm, etc.; D90 is 23μm-27μm, for example, it can be 23μm, 23.5μm, 24μm, 24.5μm, 25μm, 25.5μm, 26μm, 26.5μm or 27μm, etc.
[0019] Preferably, the particle size of the positive electrode material satisfies: D50 is 8μm-14μm, for example, it can be 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 13μm or 14μm, etc.; D90 is 18μm-22μm, for example, it can be 18μm, 18.5μm, 19μm, 19.5μm, 20μm, 20.5μm, 21μm or 22μm, etc.
[0020] Preferably, the ratio of the particle size D50 of the lithium supplement agent to the positive electrode material is 0.8-1.2, for example, 0.8, 0.85, 0.9, 1.0, 1.1 or 1.2, preferably 0.9-1.1. It should be noted that the "positive electrode material" here refers to the positive electrode material with the same crystal structure as the lithium supplement agent.
[0021] If the particle size difference between the lithium supplement and the positive electrode material is large, it may cause the adhesion of the coating to decrease, affecting the service life and reliability of the product, and then increase the corrosion of the coating, affecting the safety of the product.
[0022] Preferably, taking the total mass of the first conductive agent and the lithium supplement agent as 100%, the mass proportion of the lithium supplement agent is 0%-60% and does not include 0%, for example, it can be 0.5%, 1%, 3%, 5%, 6%, 8%, 10%, 13%, 14%, 16%, 18%, 20%, 22%, 25%, 27%, 30%, 33%, 36%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 56%, 58% or 60%, etc., preferably 5%-15%.
[0023] Since the lithium supplement has poor conductivity, it is necessary to adopt a strategy of co-incorporating it with a conductive agent. By optimizing the ratio of the lithium supplement and the conductive agent, the electrochemical performance of the positive electrode can be improved.
[0024] Preferably, the conductive coating is a carbon coating layer.
[0025] Preferably, the first conductive agent includes at least one of carbon black, Ketjen black and acetylene black.
[0026] Preferably, the conductive coating further includes a first binder.
[0027] Preferably, the first binder comprises at least one of acrylate, polyacrylic acid (PAA), modified polyacrylic acid or waterborne polyurethane, preferably modified polyacrylic acid.
[0028] In the present invention, modified polyacrylic acid refers to a class of materials whose molecular structure is modified by chemical modification or physical modification to improve its performance and application value. For example, the conductivity and thermal stability of PAA glue can be increased by modification.
[0029] Preferably, the mass content of the first binder in the conductive coating is 6%-15%, for example, it can be 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 11%, 11.5%, 12%, 12.5%, 13%, 14%, 14.5% or 15%, etc.
[0030] Preferably, the carbon coating layer has a thickness of 0.3 μm-2 μm, for example, 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 1.7 μm, 1.8 μm or 2 μm.
[0031] In the present invention, the conductive coating is relatively thin, and the addition of lithium supplementing material will not affect the mechanical stability of the positive electrode.
[0032] Preferably, the positive electrode material layer includes a positive electrode material, a second conductive agent and a second binder.
[0033] The present invention does not specifically limit the types of the second conductive agent and the second binder, and the mass ratio of the positive electrode material, the second conductive agent and the second binder. Those skilled in the art may make their selections by referring to the relevant techniques for preparing the positive electrode material layer in the prior art, and the present invention does not specifically limit them.
[0034] In a second aspect, the present invention provides a method for preparing a positive electrode as described in the first aspect, the preparation method comprising the following steps:
[0035] (1) dispersing the raw materials of the conductive coating in a solvent to obtain a conductive slurry;
[0036] (2) coating the conductive slurry on the surface of the current collector substrate, and forming a conductive coating on the surface of the current collector substrate after drying to obtain a current collector;
[0037] (3) coating an active slurry on the conductive coating of the current collector, and forming a positive electrode material layer on the surface of the conductive coating after drying to obtain a positive electrode;
[0038] Wherein, the raw materials of the conductive coating include a first conductive agent and a lithium supplement agent.
[0039] The method of the invention has simple preparation steps, requires less equipment, has low maintenance and production costs, and is conducive to popularization and application.
[0040] Preferably, the raw materials of the conductive coating in step (1) also include a first binder.
[0041] Preferably, the first binder includes at least one of acrylate, polyacrylic acid, modified polyacrylic acid or waterborne polyurethane, preferably modified polyacrylic acid.
[0042] Preferably, the first binder is a modified polyacrylic acid glue with a solid content of 15%-30%, for example, 15%, 16%, 17%, 18%, 20%, 22%, 24%, 25%, 26%, 28% or 30%, etc.; the viscosity of the modified polyacrylic acid is 200mPa.s-1500mPa.s, for example, 200mPa.s, 300mPa.s, 400mPa.s, 500mPa.s. s, 550mPa.s, 600mPa.s, 650mPa.s, 700mPa.s, 750mPa.s, 800mPa.s, 850mPa.s, 900mPa.s, 950 mPa.s, 1000mPa.s, 1050mPa.s, 1100mPa.s, 1200mPa.s, 1300mPa.s, 1400mPa.s or 1500mPa.s, etc.
[0043] Preferably, the raw materials for the carbon coating layer in step (1) also include a wetting agent.
[0044] Preferably, the wetting agent comprises at least one of polyether siloxane, modified polyether siloxane and alcohols, preferably modified polyether siloxane.
[0045] In the present invention, modified polyether siloxane refers to a class of materials whose molecular structure is modified by chemical modification or physical modification to improve its performance and application value. Generally, the lipophilicity, hydrophilicity and thermal stability of polyether siloxane materials are improved by modification.
[0046] Preferably, the amount of the wetting agent is 5%-20% of the total mass of the reaction system, for example, 5%, 6%, 8%, 9%, 10%, 12%, 14%, 15%, 16%, 18% or 20%, etc. Here, the total mass of the reaction system refers to the mass of all liquids after the wetting agent is added.
[0047] In one embodiment, the solvent in step (1) is water, preferably deionized water.
[0048] As a preferred technical solution of the preparation method of the present invention, step (1) comprises:
[0049] S1. Add a first conductive agent and a lithium supplement agent to the adhesive glue solution, disperse them, and obtain a first material;
[0050] S2: adding a wetting agent to the first material, stirring and then sand-milling to obtain a conductive slurry.
[0051] Preferably, the solid content of the adhesive solution in step S1 is 15%-25%, for example, it can be 15%, 17%, 18%, 20%, 22%, 23%, 24% or 25%.
[0052] Preferably, step S1 comprises: firstly adding a part of the first conductive agent and a part of the lithium supplement agent to the binder glue solution, performing a first high-speed dispersion, and then adding the remaining first conductive agent and the lithium supplement agent to the obtained material, performing a second high-speed stirring.
[0053] In the present invention, by adding the conductive agent twice, the problem that the viscosity of the slurry is too high and cannot be stirred due to the large amount of conductive agent (such as carbon black) added all at once can be avoided. Adding the lithium supplement agent twice can increase the uniformity of the lithium supplement agent in the slurry.
[0054] Preferably, the portion of the first conductive agent accounts for 40%-60% of the total conductive agent, for example, it may be 40%, 42%, 44%, 46%, 48%, 50%, 52%, 53%, 55%, 57% or 60%, etc.
[0055] Preferably, the portion of lithium supplement accounts for 40%-60% of the total amount of lithium supplement, for example, it can be 40%, 42%, 44%, 46%, 48%, 50%, 52%, 53%, 55%, 57% or 60%, etc.
[0056] Preferably, the rotation speed of the first high-speed stirring is 2000rpm-2600rpm, for example, it can be 2000rpm, 2100rpm, 2150rpm, 2200rpm, 2250rpm, 2300rpm, 2350rpm, 2400rpm, 2500rpm, 2550rpm or 2600rpm.
[0057] Preferably, the time for the first high-speed stirring is 30 min-60 min, for example, it can be 20 min, 22 min, 25 min, 27 min, 30 min, 35 min, 38 min, 40 min, 43 min, 46 min, 48 min, 50 min, 53 min, 56 min or 60 min, etc.
[0058] Preferably, the rotation speed of the second high-speed stirring is 2000rpm-2600rpm, for example, it can be 2000rpm, 2100rpm, 2150rpm, 2200rpm, 2250rpm, 2300rpm, 2350rpm, 2400rpm, 2500rpm, 2550rpm or 2600rpm.
[0059] Preferably, the time for the second high-speed stirring is 30 min-60 min, for example, it can be 20 min, 22 min, 25 min, 27 min, 30 min, 35 min, 38 min, 40 min, 43 min, 46 min, 48 min, 50 min, 53 min, 56 min or 60 min, etc.
[0060] Preferably, the stirring speed in step S2 is 10 rpm-15 rpm, for example, it can be 10 rpm, 11 rpm, 12 rpm, 13 rpm or 15 rpm.
[0061] Preferably, the stirring time in step S2 is 30 min-45 min, for example, it can be 30 min, 35 min, 38 min, 40 min, 43 min or 45 min.
[0062] Preferably, the number of sand grinding in step S2 is 4 to 8 times, for example, 4, 5, 6, 7 or 8 times. Those skilled in the art can adjust the number of sand grinding according to the particle size requirements of the slurry.
[0063] Preferably, the parameters of the sanding in step S2 are: the sanding speed is 800r / min-1200r / min, for example, it can be 800r / min, 850r / min, 900r / min, 950r / min, 1000r / min, 1050r / min, 1100r / min, 1150r / min or 1200r / min, etc.; the sanding time is 5min-15min, for example, it can be 5min, 8min, 10min, 12min or 15min, etc.
[0064] In a third aspect, the present invention provides a lithium battery, comprising the positive electrode described in the first aspect.
[0065] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0066] Compared with the prior art, the present invention has the following beneficial effects:
[0067] The present invention introduces and uses a specific type of lithium replenisher in the carbon coating layer and uses it in combination with the first conductive agent, so that the carbon coating layer not only plays its role in improving the conductivity of the positive electrode, but also has the function of replenishing lithium. This method basically does not affect the electrical performance of the battery, and at the same time has a good lithium replenishing effect, replenishing the lithium ions missing in the lithium battery during the first operation and subsequent cycles, avoiding lithium ion loss, enabling the lithium battery to have a higher initial efficiency, and effectively increasing the cycle life of the battery and the energy density during operation. DETAILED DESCRIPTION
[0068] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0069] The embodiments of the present invention are described in detail below so that the advantages and features of the invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0070] In the embodiment of the present invention, the modified polyacrylic acid glue was purchased from Sinopharm Chemical Reagent Co., Ltd., with an average molecular weight of MW-5000 and a solid content of 20%.
[0071] The surface capacity of the positive electrode sheets prepared in Examples 1-12 and Comparative Examples 1-3 of the present invention is 4 mAh / 100 cm 2 .
[0072] Example 1
[0073] This embodiment provides a positive electrode sheet, comprising a carbon-coated current collector and a positive electrode material layer coated on the surface of the carbon-coated current collector, wherein the carbon-coated current collector comprises a current collector substrate and a carbon coating layer (with a thickness of 0.5 μm) disposed on the current collector substrate, wherein the carbon coating layer comprises a first conductive agent, a first binder and a lithium replenisher, and the positive electrode material layer comprises a positive electrode material, a second conductive agent and a second binder, wherein the lithium replenisher and the positive electrode material are substances of the same crystal structure;
[0074] Among them, the current collector substrate is aluminum foil, the first conductive agent is carbon black, the first binder is modified polyacrylic acid, the lithium supplement agent is lithium iron phosphate (D50 is 130μm, D90 is 25μm), the mass ratio of the first conductive agent and the lithium supplement agent is 90:10, the mass content of the first binder in the carbon coating layer is 10%, the positive electrode material is lithium iron phosphate (D50 is 12μm, D90 is 20μm), the second conductive agent is graphite, the second binder is PVDF, the mass ratio of the positive electrode material, the second conductive agent and the second binder is 96:2:2, and the ratio of the particle size D50 of the lithium supplement agent to the positive electrode material is 1.08.
[0075] This embodiment also provides a method for preparing the above-mentioned positive electrode sheet, comprising the following steps:
[0076] (1) providing a first adhesive glue (modified polyacrylic acid glue, solid content 20%, viscosity 1000 mPa.s);
[0077] (2) adding half of the first conductive agent and half of the lithium supplement agent to the first binder glue of step (1), dispersing at a high speed of 2500 rpm for 40 min in a 200 L double star stirring tank, then adding the remaining conductive agent and lithium supplement agent, and continuing to disperse at a high speed of 2500 rpm for 40 min to obtain a first material;
[0078] (3) adding a wetting agent (modified polyether siloxane) to the first material, wherein the wetting agent accounts for 10% of the total mass of the reaction system, and stirring at a low speed of 10 rpm for 40 min to obtain a slurry;
[0079] (4) Transfer the slurry into a sand mill and sand grind it 6 times;
[0080] (5) The sand-milled slurry is uniformly coated on an aluminum foil, and after drying, a carbon-coated current collector is obtained;
[0081] (6) dissolving the positive electrode material, the second conductive agent and the second binder in NMP to obtain a positive electrode slurry;
[0082] (7) The positive electrode slurry is evenly coated on the surface of the carbon-coated current collector, and the positive electrode sheet is obtained after drying.
[0083] A microscopic picture of the carbon coating layer was obtained through a scanning electron microscope, and then an energy spectrum was taken of the picture to observe the incorporation of lithium supplements at the microscopic level: it was found that the lithium element can be evenly dispersed on the large spherical carbon black particles. This close interaction promotes the efficient transmission of electrons and lithium ions, and provides sufficient sacrificial lithium ions for the first charge and discharge of the lithium battery, thereby increasing the electrical conductivity and electrical properties of the lithium battery.
[0084] Example 2
[0085] The difference between this embodiment and embodiment 1 is that the mass ratio of the first conductive agent to the lithium supplement agent is 80:20.
[0086] Example 3
[0087] The difference between this embodiment and embodiment 1 is that the mass ratio of the first conductive agent to the lithium supplement agent is 70:30.
[0088] Example 4
[0089] The difference between this embodiment and embodiment 1 is that the mass ratio of the first conductive agent to the lithium supplement agent is 60:40.
[0090] Example 5
[0091] The difference between this embodiment and embodiment 1 is that the mass ratio of the first conductive agent to the lithium supplement agent is 50:50.
[0092] Example 6
[0093] The difference between this embodiment and embodiment 1 is that the mass ratio of the first conductive agent to the lithium supplement agent is 40:60.
[0094] Example 7
[0095] The difference between this embodiment and embodiment 1 is that the lithium supplement is lithium manganese iron phosphate (chemical formula is LiFe 0.5 Mn 0.5 PO4), the positive electrode material is lithium iron phosphate.
[0096] Example 8
[0097] The difference between this embodiment and embodiment 1 is that the lithium supplement is ternary lithium (chemical formula is LiNi 0.8 Co 0.15 Mn 0.05 O2), the positive electrode material is ternary lithium (chemical formula is LiNi 0.8 Co 0.15 Mn 0.05 O2).
[0098] Example 9
[0099] This embodiment provides a positive electrode sheet, comprising a carbon-coated current collector and a positive electrode material layer coated on the surface of the carbon-coated current collector, wherein the carbon-coated current collector comprises a current collector substrate and a carbon coating layer (with a thickness of 1.5 μm) disposed on the current collector substrate, wherein the carbon coating layer comprises a first conductive agent, a first binder and a lithium replenisher, and the positive electrode material layer comprises a positive electrode material, a second conductive agent and a second binder, wherein the lithium replenisher and the positive electrode material are substances of the same crystal structure;
[0100] Among them, the current collector substrate is aluminum foil, the first conductive agent is carbon black, the first binder is modified polyacrylic acid, the lithium supplement agent is lithium iron phosphate (D50 is 15μm, D90 is 27μm), the mass ratio of the first conductive agent and the lithium supplement agent is 80:20, the mass content of the first binder in the carbon coating layer is 6%, the positive electrode material is lithium iron phosphate (D50 is 10μm, D90 is 22μm), the second conductive agent is graphite, the second binder is PVDF, the mass ratio of the positive electrode material, the second conductive agent and the second binder is 96:2:2, and the ratio of the particle size D50 of the lithium supplement agent to the positive electrode material is 1.5.
[0101] This embodiment also provides a method for preparing the above-mentioned positive electrode sheet, comprising the following steps:
[0102] (1) providing a first adhesive glue (modified polyacrylic acid glue, solid content 20%, viscosity 1000 mPa.s);
[0103] (2) adding half of the first conductive agent and half of the lithium supplement agent to the first binder glue of step (1), dispersing at a high speed of 2000 rpm for 60 min in a 200 L double star stirring tank, then adding the remaining conductive agent and lithium supplement agent, and continuing to disperse at a high speed of 2600 rpm for 30 min to obtain a first material;
[0104] (3) adding a wetting agent (modified polyether siloxane) to the first material, wherein the wetting agent accounts for 5% of the total mass of the reaction system, and stirring at a low speed of 15 rpm for 30 min to obtain a slurry;
[0105] (4) Transfer the slurry into a sand mill and sand grind for 7 times;
[0106] (5) The sand-milled slurry is uniformly coated on an aluminum foil, and after drying, a carbon-coated current collector is obtained;
[0107] (6) dissolving the positive electrode material, the second conductive agent and the second binder in NMP to obtain a positive electrode slurry;
[0108] (7) The positive electrode slurry is evenly coated on the surface of the carbon-coated current collector, and the positive electrode sheet is obtained after drying.
[0109] Example 10
[0110] This embodiment provides a positive electrode sheet, comprising a carbon-coated current collector and a positive electrode material layer coated on the surface of the carbon-coated current collector, wherein the carbon-coated current collector comprises a current collector substrate and a carbon coating layer (with a thickness of 2 μm) disposed on the current collector substrate, wherein the carbon coating layer comprises a first conductive agent, a first binder and a lithium replenisher, and the positive electrode material layer comprises a positive electrode material, a second conductive agent and a second binder, wherein the lithium replenisher and the positive electrode material are substances of the same crystal structure;
[0111] Among them, the current collector substrate is aluminum foil, the first conductive agent is carbon black, the first binder is modified polyacrylic acid, the lithium supplement agent is lithium iron phosphate (D50 is 17μm, D90 is 25μm), the mass ratio of the first conductive agent and the lithium supplement agent is 97:3, the mass content of the first binder in the carbon coating layer is 6%, the positive electrode material is lithium iron phosphate (D50 is 8μm, D90 is 18μm), the second conductive agent is graphite, the second binder is PVDF, the mass ratio of the positive electrode material, the second conductive agent and the second binder is 96:2:2, and the ratio of the particle size D50 of the lithium supplement agent to the positive electrode material is 2.13.
[0112] This embodiment also provides a method for preparing the above-mentioned positive electrode sheet, comprising the following steps:
[0113] (1) providing a first adhesive glue (modified polyacrylic acid glue, solid content 20%, viscosity 1000 mPa.s);
[0114] (2) adding half of the first conductive agent and half of the lithium supplement agent to the first binder glue of step (1), dispersing at a high speed of 2300 rpm for 50 min in a 200 L double star stirring tank, then adding the remaining conductive agent and lithium supplement agent, and continuing to disperse at a high speed of 2200 rpm for 40 min to obtain a first material;
[0115] (3) adding a wetting agent (modified polyether siloxane) to the first material, wherein the wetting agent accounts for 20% of the total mass of the reaction system, and stirring at a low speed of 10 rpm for 45 min to obtain a slurry;
[0116] (4) Transfer the slurry into a sand mill and sand grind it 6 times;
[0117] (5) The sand-milled slurry is uniformly coated on an aluminum foil, and after drying, a carbon-coated current collector is obtained;
[0118] (6) dissolving the positive electrode material, the second conductive agent and the second binder in NMP to obtain a positive electrode slurry;
[0119] (7) The positive electrode slurry is evenly coated on the surface of the carbon-coated current collector, and the positive electrode sheet is obtained after drying.
[0120] Embodiment 11
[0121] The difference between this embodiment and embodiment 1 is that in the preparation method of the positive electrode, step (2) is: add all the first conductive agent and all the lithium supplement agent to the binder glue of step (1), and disperse them at a high speed of 2500 rpm for 80 minutes in a 200L Double Star stirring tank to obtain a first material.
[0122] Example 12
[0123] The particle size D50 of the lithium supplementer is 15 μm, and D90 is 27 μm. The particle size D50 of the positive electrode material is 9 μm, and D90 is 19 μm. Therefore, the ratio of the particle size D50 of the lithium supplementer to that of the positive electrode material is 1.66.
[0124] Comparative Example 1
[0125] The difference between this comparative example and Example 1 is that the mass ratio of the first conductive agent to the lithium supplement agent is 100:0.
[0126] Comparative Example 2
[0127] The difference between this comparative example and Example 1 is that the lithium supplement agent is replaced by LiCl.
[0128] Comparative Example 3
[0129] The difference between this comparative example and Example 1 is that the lithium supplement agent is replaced by LiOH.
[0130] Full battery assembly:
[0131] Preparation of negative electrode:
[0132] The negative electrode active material (graphite), conductive carbon black Super P, and binder CMC were mixed in a mass ratio of 90:7:3 and uniformly mixed with pure water to prepare a negative electrode slurry; the negative electrode slurry was uniformly coated on both surfaces of the negative electrode current collector (carbon-coated copper foil) to form a negative electrode active coating, and dried at 100°C for 1 hour under a vacuum environment, and then cold pressed and cut to obtain a negative electrode with a surface capacity of 4 mAh / 100 cm 2 The negative electrode.
[0133] Preparation of diaphragm:
[0134] A PP film with a thickness of 15 μm and coated with a ceramic layer on one side was used as the separator.
[0135] Preparation of electrolyte:
[0136] Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are uniformly mixed in a volume ratio of 1:1:1 to obtain a solvent, and LiPF6 is dissolved in the solvent to obtain an electrolyte with a concentration of 1 mol / L.
[0137] Battery Assembly
[0138] The positive electrode sheets of Examples 1-12 and Comparative Examples 1-3 were stacked in order with the separator and the negative electrode sheet, respectively, and injected with electrolyte. After vacuum packaging, standing, forming, and shaping steps, a battery was obtained.
[0139] Button type symmetrical battery assembly:
[0140] Except for replacing the negative electrode sheet with a lithium metal negative electrode sheet, other methods and conditions are the same as the full battery assembly.
[0141] Performance test: The first efficiency test of the whole battery is carried out: at 25°C, the lithium ion battery prepared by using the positive electrode sheets of Examples 1-12 and Comparative Examples 1-3 is charged and discharged for the first time at a current of 0.5C (i.e., the current value of completely discharging the theoretical capacity within 2 hours). The charging is constant current and constant voltage charging, the termination voltage is 4.2V, the cut-off current is 0.05C, and the discharge termination voltage is 2.8V. Then the battery is left for 24 hours and charged to 3.85V at 0.5C constant current and constant voltage. Then the first efficiency is calculated and recorded, the first efficiency (η) = (charging capacity / charging time) / (battery set capacity / charging time).
[0142] The button-type symmetrical battery was tested for cycle capacity retention rate: the button-type symmetrical battery was tested at room temperature (25°C), the button-type symmetrical battery was charged to 4.2V at a constant current and constant voltage rate of 3C, and the cut-off current was 3C, and then the button-type symmetrical battery was discharged to 0V at a constant current rate of 3C, which was considered one charge and discharge cycle. The button-type symmetrical battery was charged and discharged for 100 cycles in accordance with the above method, and the discharge capacity of the button-type symmetrical battery before and after the cycle was tested. The capacity retention rate of the button-type symmetrical battery after 100 cycles was calculated according to the following formula: Capacity retention rate after 100 cycles (%) = (discharge capacity of the 100th cycle / first discharge capacity) × 100%.
[0143] The results are shown in Table 1.
[0144] Table 1
[0145] serial number First effect% Cycle capacity retention rate % Example 1 79.0 72.6 Example 2 83.0 77.9 Example 3 89.1 81.2 Example 4 92.4 88.5 Example 5 84.1 80.7 Example 6 80.4 73.2 Example 7 78.3 70.5 Example 8 76.3 69.5 Example 9 75.3 68.3 Example 10 74.6 66.1 Embodiment 11 72.8 65.2 Example 12 70.8 63.7 Comparative Example 1 62.8 51.5 Comparative Example 2 60.3 55.2 Comparative Example 3 67.3 52.7
[0146] As can be seen from Table 1, the present invention can improve the performance of the positive electrode by introducing and using a specific type of lithium supplement agent in the carbon coating layer and using it in combination with the first conductive agent. The lithium battery assembled using the positive electrode has a higher first efficiency, cycle life and energy density during operation.
[0147] By comparing Examples 1-6, it can be seen that when the mass ratio of the first conductive agent to the lithium supplement agent is (50%-70%): (30%-50%), the lithium battery has better first-efficiency and cycle performance. When the mass ratio of the first conductive agent to the lithium supplement agent is 60:40, the lithium battery has the best first-efficiency performance and the longest cycle stability, that is, it exhibits the best battery electrical performance. Comparative Example 1 does not add a lithium supplement agent, and the corresponding lithium battery exhibits poor electrical performance, which is far from the performance of the positive electrode supplemented with lithium in Examples 1 to 12.
[0148] By comparing Example 1 with Example 11, it can be seen that the slurry needs to be fully and evenly dispersed. If the slurry is not evenly dispersed, the battery performance will not meet the standards.
[0149] By comparing Example 1 with Example 12, it can be seen that the difference between the particle sizes of the positive electrode material and the lithium supplement agent is too large, which will lead to uneven particle sizes under microscopic conditions and uneven coating.
[0150] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A positive electrode, characterized in that The positive electrode includes a current collector and a positive electrode material layer coated on the surface of the current collector, the positive electrode material layer includes a positive electrode material, the current collector includes a current collector substrate and a conductive coating arranged on the current collector substrate, the conductive coating includes a first conductive agent and a lithium replenisher, and at least one of the positive electrode materials and the lithium replenisher has the same crystal structure.
2. The positive electrode according to claim 1, characterized in that The crystal structure is selected from any one of a layered structure, a spinel structure or an olivine structure; Preferably, the particle size of the lithium supplement agent satisfies: D50 is 13 μm-17 μm, D90 is 23 μm-27 μm; Preferably, the particle size of the positive electrode material satisfies: D50 is 8 μm-14 μm, and D90 is 18 μm-22 μm; Preferably, the ratio of the particle size D50 of the lithium supplement agent to the particle size D50 of the positive electrode material is 0.8-1.2, preferably 0.9-1.1; Preferably, based on the total mass of the first conductive agent and the lithium supplement agent being 100%, the mass proportion of the lithium supplement agent is 0%-60% and does not include 0%, preferably 5%-15%; Preferably, the first conductive agent includes at least one of carbon black, Ketjen black and acetylene black.
3. The positive electrode according to claim 1 or 2, characterized in that The conductive coating is a carbon coating layer; Preferably, the conductive coating further comprises a first binder; Preferably, the first binder comprises at least one of acrylate, polyacrylic acid, modified polyacrylic acid or waterborne polyurethane, preferably modified polyacrylic acid; Preferably, the mass content of the first binder in the carbon coating layer is 6%-15%; Preferably, the thickness of the conductive coating is 0.3 μm-2 μm.
4. A method for preparing a positive electrode according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) dispersing the raw materials of the conductive coating in a solvent to obtain a conductive slurry; (2) coating the conductive slurry on the surface of the current collector substrate, and forming a conductive coating on the surface of the current collector substrate after drying to obtain a current collector; (3) coating an active slurry on the conductive coating of the current collector, and forming a positive electrode material layer on the surface of the conductive coating after drying to obtain a positive electrode; Wherein, the raw materials of the conductive coating include a first conductive agent and a lithium supplement agent.
5. The preparation method according to claim 4, characterized in that: The raw materials of the conductive coating in step (1) further include a first binder, and the first binder is a binder glue; Preferably, the first binder comprises at least one of acrylate, polyacrylic acid, modified polyacrylic acid or waterborne polyurethane, preferably modified polyacrylic acid; Preferably, the first binder is a modified polyacrylic acid glue having a solid content of 15%-30%, and the viscosity of the modified polyacrylic acid is 200mPa.s-1500mPa.s.
6. The preparation method according to claim 4 or 5, characterized in that: The raw materials of the conductive coating in step (1) also include a wetting agent; Preferably, the wetting agent comprises at least one of polyether siloxane, modified polyether siloxane and alcohols, preferably modified polyether siloxane; Preferably, the amount of the wetting agent is 5%-20% of the total mass of the reaction system.
7. The preparation method according to any one of claims 4 to 6, characterized in that: Step (1) comprises: S1. Add a first conductive agent and a lithium supplement agent to a binder glue solution, disperse them, and obtain a first material; S2: adding a wetting agent to the first material, stirring and then sand-milling to obtain a conductive slurry.
8. The preparation method according to claim 7, characterized in that: The solid content of the adhesive solution in step S1 is 15%-25%; Preferably, step S1 comprises: firstly adding a part of the first conductive agent and a part of the lithium supplement agent to the binder glue solution, performing a first high-speed dispersion, then adding the remaining first conductive agent and the lithium supplement agent to the obtained material, and performing a second high-speed stirring; Preferably, the portion of the first conductive agent accounts for 40%-60% of the total amount of the conductive agent; Preferably, the portion of lithium supplement accounts for 40%-60% of the total amount of lithium supplement; Preferably, the rotation speed of the first high-speed stirring is 2000r / min-2600r / min; Preferably, the first high-speed stirring time is 30min-60min; Preferably, the rotation speed of the second high-speed stirring is 2000r / min-2600r / min; Preferably, the second high-speed stirring time is 30 min-60 min.
9. The preparation method according to claim 7 or 8, characterized in that: The stirring speed in step S2 is 10rpm-15rpm; Preferably, the stirring time in step S2 is 30 min-45 min; Preferably, the number of sanding in step S2 is 4 to 8 times; Preferably, the parameters of the sanding in step S2 are: the sanding speed is 800r / min-1200r / min, and the sanding time is 5min-15min.
10. A lithium battery, characterized in that: The lithium battery comprises the positive electrode according to any one of claims 1 to 3.
Citation Information
Patent Citations
A silicon-containing high-energy-density lithium-ion battery
CN109713367B